Manejo de sepsis neonatal en el Hospital Infantil de Morelia "Eva Sámano de López Mateos" durante seis meses - Romero Quiros, Nancy (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
Neonatal sepsis has a great impact, in Michoacán during 2016, 362 neonatal deaths were reported, of which 48 were due to infections. There is no consensus worldwide or unified criteria, which makes the suspicion, diagnosis and treatment difficult. Objectives: To analyze the management of neonatal sepsis in the Morelia Children's Hospital during the period April-September 2018, to estimate the frequency of neonatal sepsis by gestational age, sex, birth weight, knowing the risk factors of sepsis, identifying the main clinical manifestations and alterations in laboratory studies, as well as describing the established treatment, causative microorganisms and evolution of cases. Material and methods: Prospective, observational, descriptive, cross-sectional study and without risk. All newborns hospitalized with suspected sepsis or diagnosis were included in the Neonatal Intensive Care Unit of the Children's Hospital of Morelia during the period from April 1st to 30th of September. The data obtained were analyzed with the statistical program SPSS version 23 with analysis of descriptive statistics. Results: Thirty-three patients with a diagnosis of sepsis were registered (incidence 22.91%), 12 women (36.4%) and 21 men (63.6%), female-male ratio 1.75: 1. 54% of cases were preterm, with a higher percentage of early neonatal sepsis (54.5%). The main risk factors were the use of central venous catheter and placement of probes (81.8%), infections during pregnancy (78.7%), prematurity and low birth weight (54.5%). The clinical manifestations were presented at the respiratory level in 84.8% of the cases, cardiocirculatory with 66.7% of the cases and thirdly the digestive signs with 57.6%. The respiratory distress data were presented in 72.7%, followed by hypoactivity (51.5%) and fever (39.4%).

La sepsis neonatal tiene un gran impacto, en Michoacán durante el 2016 se reportaron 362 muertes neonatales de las cuales 48 fueron por infecciones. No se cuenta con un consenso a nivel mundial o criterios unificados, lo que dificulta la sospecha, diagnóstico y tratamiento. Objetivos: Analizar el manejo de sepsis neonatal en el hospital infantil de Morelia durante el periodo abril-septiembre 2018, estimar la frecuencia de sepsis neonatal por edad gestacional, sexo, peso al nacimiento, frecuencia de sepsis neonatal temprana y tardía, conocer los factores de riesgo de sepsis, identificar las principales manifestaciones clínicas y alteraciones en estudios de laboratorio así como describir el tratamiento establecido, microrganismos causales y evolución de los casos. Material y métodos: Estudio prospectivo, observacional, descriptivo, transversal y sin riesgo. Se incluyeron todos los recién nacidos hospitalizados con sospecha de sepsis o diagnostico en la unidad de cuidados intensivos neonatales del H. Infantil de Morelia en el período comprendido del 01 se abril al 30 de septiembre del 2018. Los datos obtenidos se analizaron con el programa estadístico SPSS versión 23 realizándose análisis de estadística descriptiva. Resultados: Se registraron 33 pacientes con diagnóstico de sepsis (incidencia 22.91%,) 12 mujeres (36.4%) y 21 hombres (63.6%), relación mujer/hombre 1.75:1. 54% de los casos fue pretérmino, con mayor porcentaje de sepsis neonatal temprana (54.5%). Los principales factores de riesgo fueron el uso de catéter venoso central y colocación de sondas (81.8%), infecciones durante el embarazo (78.7%) prematurez y bajo peso al nacer (54.5%). Las manifestaciones clínicas se presentaron a nivel respiratorio en el 84.8% de los casos, cardiocirculatorio con 66.7% de los casos y en tercer lugar los signos digestivos con 57.6%. Los datos de dificultad respiratoria se presentaron en el 72.7%, seguidos de hipoactividad (51.5%) y fiebre (39.4%).
Facultad de Ciencias Médicas y Biológicas. Especialidad en Pediatría
Keywords: info:eu-repo/classification/cti/3; FCMB-E-2019-0255; Epidemiología; Etiología; Mortalidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4316